Reticence to Speak English: Lived Experiences of the Teacher Education Students - Joy S. Jungco, Shelly; Karyl P. Maligang, Audrey; Malubay, Lennie; Jane V. Esimos, Mary (International Journal of Scientific Research and Management (IJSRM), 2022)
AbstractThe purpose of this study was to investigate the lived-experiences of the Teacher Education students of the Northern Iloilo Polytechnic State College, Estancia, Iloilo, Philippines in terms of being reticent to speak English. Specifically, the study explored the following research questions: what are the lived- experiences of students in terms of being reticent to speak English? and what insights and meaning to Teacher Education students’ reticence to speak English may be revealed by their lived experiences? This study used the qualitative research design, particularly the phenomenological research approach. Themes and eidetic insights were established to describe the lived experiences of the students and the recommendations were also made by the researcher. The themes presented in this study were: (1) Low proficiency in the target language. (2) Silence as an innate characteristic. (3) Unwillingness to communicate due to shyness and fears. (4) A need for a formation of a speaking habit. (5) Reluctant to speak due to difficulty in pronunciation. (6) A need for focus and memory exercise. (7) A need for wait-time to speak their minds. (8) Perceived reticence in the classroom: a need for proper conditioning. It can be noted that students’ reticence to speak English were due to the following reasons: low level of English proficiency, shyness, fears, pronunciation difficulty, poor speaking habit, poor memory, innate characteristic, and poor focus. However, there exists an eidetic insight that the students’ reticence can be reduced by means of teacher’s strategies and use of classroom activities to develop their oral fluency and participation.